Radiative recombination of the PVK/C60 molecular complexes with the radiation damages - Коbus, E.S.; Dmytrenko, O.P.; Kulish, N.P.; Prylutskyy, Yu.I.; Belyy, N.M.; Syromyatnikov, V.G.; Studzinskyy, S.L.; Zabolotnyy, M.A.; Gryn'ko, D.A.; Shchur, D.V.; Shlapatskaya, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The relaxation processes of electronic excitations in the films composed from
a mixture of the amorphous semiconductors of polyvinylcarbazole and C₆₀ fullerenes
(PVC/C₆₀) with different contents of nanocluster molecules and beyond the threshold
electron irradiation are studied. It is shown that, in the entire range of the concentrations
of C₆₀ molecules, for which the molecular disperse state of a mixture retains, the
complexes with the charge transfer due to the photogeneration of electron-hole pairs are
observed in the PVC/C₆₀ films. The photoluminescence spectra indicate the presence of
both the molecular emitting transitions and the recombination luminescence caused by
the electron transfer in the composition of excitons from the matrix to impurity
fullerenes. Depending on the content of C₆₀ molecules, the photoluminescence spectra
are substantially reconstructed, reflecting the changes in the electron structure of
molecular complexes. The nature of these changes retains with the introduction of
radiation-induced damages under high-energy electron irradiation with an absorbed dose
of 3.0 MGy.